Search for black holes and other new phenomena in high-multiplicity final states in proton–proton collisions at √s=13TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (Elsevier, 2017)
Search for black holes and other new phenomena in high-multiplicity final states in proton–proton collisions at √s = 13 TeV